PERSEPSI MAHASISWA PEROKOK DALAM MENANGGAPI PERINGATAN BAHAYA PADA BUNGKUS ROKOK: Studi Kasus Pada Mahasiswa Ilmu Kesehatan Universitas dr. Soebandi - Dechika Erian Dewi Caprianda Widayanti; Juariyah (MEDIAKOM, 2023)
This research tries to explain and describe how student smokers perceive the danger warnings on cigarette packs. This study aims to examine several factors that underlie smoking behavior among students at Dr. University. Soebandi, Jember Regency. This research was conducted using a descriptive qualitative method, which involved data mining methods through observation and interviews. A total of 7 students from the Faculty of Health Sciences, Dr. University. Soebandi, who is an active smoker, became the informant in this research. In understanding the reality of the informants, this research uses the S-O-R theory put forward by Hovland as an effort to understand the social reality in society that underlies an action. The results of the research prove that there are several factors that underlie students' smoking habits, including cultural factors, students' personal experience factors, and educational factors that underlie students' smoking habits.